Estimating Economic Values for Pigeon Island National Park, Sri Lanka: Towards Designing Economic Instruments to Minimize Anthropogenic Degradation - Jayaratne, Chamathi; Wattage, Premachandra; Gunawardena, Prasanthi (Journal of Environmental Management and Tourism, 2026)
Pigeon Island National Park (PINP), a vital Sri Lankan Marine Protected Area, faces severe anthropogenic degradation stemming from rapid post-conflict tourism growth, excessive plastic accumulation, and illegal fishing. Institutional financing failures, where tourism revenue bypasses local conservation efforts, necessitate the design of sustainable, market-based instruments. The primary objectives of this study were to examine threats, estimate visitor Marginal Willingness to Pay (MWTP) for conservation improvements, and design novel, non-tax economic instruments. The Choice Experiment Method (CEM) was employed to quantify attribute-specific visitor preferences, with face-to-face interviews conducted on a sample of 200 visitors (Jan-Aug 2022). Attributes included reductions in plastic/polythene, illegal fishing nets, crowding, and a monetary contribution (Cost). The resulting Conditional Logit Model was highly significant (p=0.000), showing a positive MWTP for all conservation attributes. Key results indicated visitors were willing to pay LKR 564.55 to reduce plastic by 50% and LKR 568.35 to reduce illegal nets by 50%. These values inform the design of a complementary package of non-tax instruments: 1) A Refundable Deposit System (LKR 564.55) for plastic to address diffuse pollution; and 2) An Annual Insurance Surcharge (LKR 568.35) on boat owners to target sectoral risk. Implementation of these instruments provides a dedicated, re-investable funding source, bypassing the socio-political friction of imposing direct taxes, and offers a crucial blueprint for PINP’s sustained ecological health.